THE QUALITY OF LENDING THE ECONOMY - GABRIELA CORINA SLUSARIUC (Annals of the University of Petrosani: Economics)
Credit has a very important role in the economy, and the evolution of national economies has become largely dependent on the private banking system. Credit policy has become one of the main means of action on the economic conjuncture, being called upon to prevent the uncorrelations and potential imbalances that may arise. Poor credit risk management can cause the banking system to collapse, with unimaginable economic, social and political consequences.